2021
DOI: 10.20529/ijme.2021.013
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative inquiry into stigma among patients with Covid-19 in Chennai, India

Abstract: ntroduction: The Covid-19 pandemic has left a serious impact on the lives of people globally. One key social consequence of the infection has been the stigma associated with it. Objectives: This study was conducted to explore the lived experiences of stigma among persons who have recovered from Covid-19 in Chennai, India. Methods: In depth telephonic interviews were conducted among 12 persons who had recovered from Covid-19 in Chennai. The participants were encouraged to narrate their experiences of stigma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Stigma can also act as a risk factor for anxiety and depression of the affected individual. 12 , 21 , 22 COVID-19-related stigma can also contribute to depression in nonaffected individuals. 23 Anticipatory stigma refers to the affected person’s fear about how society will react to them after their recovery.…”
mentioning
confidence: 99%
“…Stigma can also act as a risk factor for anxiety and depression of the affected individual. 12 , 21 , 22 COVID-19-related stigma can also contribute to depression in nonaffected individuals. 23 Anticipatory stigma refers to the affected person’s fear about how society will react to them after their recovery.…”
mentioning
confidence: 99%
“…In a qualitative study on individuals who have recovered from COVID-19 infection, the usual manifestations of stigma were rejection from public spaces,decrease in social support, decrease in income,and physical violence. Also, some factors that exacerbated the stigma were lack of information, fear of infection, the implication of police in contact tracing, segregation, and legitimization of isolation by obliged public health interventions [35]. Some participantspresentedthe feeling ofemptiness and meaningless of life.Specialists have indicated that feelings during a pandemic are very similar to grief, and individuals experience distressand emptiness, which can result in a loss of meaning in life [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…First, COVID-19 patients suffer from verbal abuse, social isolation, and rejection 31,32 . These experiences of social stigma even spread to suspected patients 21 and can persist into the recovery stage as numerous COVID-19 survivors have reported being excluded and rejected by neighbors, public spaces, workplaces, and healthcare facilities 33 . Indeed, a largescale study involving 411 HCWs from 173 countries showed that more than one-fifth of participants perceived social stigma toward (suspected) COVID-19 patients and survivors 34 .…”
Section: Stigma Toward (Suspected) Patients and Survivorsmentioning
confidence: 99%
“…Emotion. Stigmatizers' COVID-19-related emotions (e.g., fear 33,63,67,73,74,75,76 , and anxiety 76 ) influence their stigmatizing attitudes because stigmatization is used as a coping mechanism for negative emotions arising from the pandemic. COVID-19 induces a lot of negative emotions (e.g., fear, anxiety, and anger), and individuals use stigmatization as a coping strategy to deal with these negative emotions 74 .…”
Section: Stigmatizermentioning
confidence: 99%
See 1 more Smart Citation